Nominal compounds with mobile stress in Lithuanian dialects - Bukelskytė-Čepelė, Kristina (Baltistica, 2021)
The article describes nominal compounds assigned to mobile accent paradigm 3 (AP3) that are found in Lithuanian dialects. In these compounds, the stress alternates between the last and the first syllables, and it is assumed that they were assigned to the mobile accent paradigm due to the spread of secondary mobility. It is suggested that in Lithuanian dialects secondary mobility may arise in compounds with initial stress and, as a result, accentual variants with fixed stress and mobile stress exist in the same dialectal areas without semantic restriction. Later examples of accentual neomobility are found in Lithuanian dialects as well. In terms of semantics, mobile compounds are mostly verbal governing compounds and determinative compounds, i.e., nouns, and there is only a small group of originally adjectival compounds, i.e., possessive compounds. Another finding of the study pertains to the formal criterion of compounds, i.e., the linking element; in East and South Aukštaitian, there is a tendency to use linking elements in mobile compounds, while in West Aukštaitian as well as Žemaitian, the largest portion of mobile compounds do not include linking elements.